2023
DOI: 10.1038/s41598-022-27285-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the microwave photon-magnon coupling strength for a planar fabricated resonator

Abstract: Planar resonators have a wide usage in modern microwave technologies and perspectives in novel quantum technologies development. As was demonstrated earlier, their utilization allows to achieve high values of microwave photon-magnon coupling strength—an important parameter in technologies of information coherent transfer from electromagnetic GHz range to the optical range. In the present work, the achievement of the high value of the microwave photon-magnon coupling strength by exploiting the increase of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 9 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Controlled magnon-photon coupling has previously been demonstrated experimentally in 3D rectangular cavities of different sizes using yttrium iron garnet (YIG) spheres with varying diameters [9,10] and in a 3D cylindrical cavity by varying the angle between the external magnetic field and the microwave field [18]. Similar physics has been demonstrated in planar-geometry resonator-based systems, which exhibit higher coupling strengths than those of the 3D cavity resonator-based systems [19][20][21][22][23], by varying the position of a YIG thin film [24] . Furthermore, it was shown that the coupling can be controlled in a split-ring resonator with a nonuniform microwave magnetic field by changing the track width of the split-ring [25].…”
Section: Introductionmentioning
confidence: 66%
“…Controlled magnon-photon coupling has previously been demonstrated experimentally in 3D rectangular cavities of different sizes using yttrium iron garnet (YIG) spheres with varying diameters [9,10] and in a 3D cylindrical cavity by varying the angle between the external magnetic field and the microwave field [18]. Similar physics has been demonstrated in planar-geometry resonator-based systems, which exhibit higher coupling strengths than those of the 3D cavity resonator-based systems [19][20][21][22][23], by varying the position of a YIG thin film [24] . Furthermore, it was shown that the coupling can be controlled in a split-ring resonator with a nonuniform microwave magnetic field by changing the track width of the split-ring [25].…”
Section: Introductionmentioning
confidence: 66%